A dimensão mística da liturgia no horizonte da metafísica zubiriana - Silva, Jucilei Lima da (2023)
The aim of this work is to make a description of liturgy’s dimension which we call mystic and how human being in all its constitutive structure experiences this dimension. And, as a consequence, it tries to describe in a mystical theological language the deployments which can and should occur in the normal life of a christian who experiences such a great reality — all this in the light of Spanish philosopher Xavier Zubiri’s metaphysics. For this task it will bar used the exploratory nature method, which enables an approach of Zubiri’s understanding of liturgy and of his thought. This leads to realize that, thanks to the human character of sentient intelligence, it is possible to formally actualize the real thing as reality in intellection. The thing becomes actual, it is here, and because it is, the human being becomes aware of it. As reality, the thing is formally in sentient intelligence, which feels that reality.